Linguistic Configuration and Socio-Pragmatic Function Analysis of Indonesian-English Code Switching - Yetty Yetty; Sri Ayu Budi Lestari; Muhammad Azwar Assiddiq; Susi Astiantih (Sekolah Tinggi Agama Islam Negeri Majene, 2022)
This research aimed to investigate the general patterns of linguistic configuration and socio-pragmatic functions of Indonesian-English code switching. It also explored the communication strategy that the Indonesian elites aim at when they do both IECS and EICS. This study used descriptive qualitative analysis. The data was collected from various speech interactions on TV program. The result shows that the linguistics configuration of Indonesian-English code switching are switch segments such as Noun Phrase (NP), Single Noun, Independent Clause, Verb and Adjective. The combinations of switch points of Indonesia-English code switching mostly occur between NP and HL suffix, between N and NP, between NP and Independent Clause, between V and NP, and Adj and N. In terms of types of code switching are namely; intraclausal (Iracla), Intraphrasal (Iraphra), Intralexical (Iralex), Interclausal and Tag. The socio-pragmatic function of Indonesian-English Code Switching based on the data using Gumperz’s model are interjection or sentence-filler, message qualification, personalization, and morphological adaptation. Furthermore, the communication strategy of code switching by Indonesian Elites is to adjust the message which they convey in order to emphasize the statement, also to attract their interlocutor so that they pay the attention to the speaker.